Historical and Geographical Reconstruction of the Figure of Dhul-Qarnayn in Surah Al-Kahf - Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi (Universitas Islam Negeri Sumatera Utara, 2026)
The identity of Dhul-Qarnayn in Surah Al-Kahf has been a perennial debate between Alexander the Great and Cyrus the Great. This study aims to reconstruct Dhul-Qarnayn's identity historically and validate his travel route using a topographical approach. This study uses critical historical methods and a comparative study of interpretations (classical and modern) combined with geographical data. The analysis shows that the characteristics of Cyrus the Great are more in line with the Qur'anic description of a just monotheist leader than Alexander, who worshipped many gods. The topographical approach identifies the